Aggregate residential demand flexibility behavior: A novel assessment framework. (March 2023) - Wonuola Olawale, Opeoluwa; Gilbert, Ben; Reyna, Janet
Highlights: A new framework assesses residential behavior related to demand flexibility. Residential demand flexibility behavior varies across the defined periods. Weather affects a few demand flexibility activities, while climate influences overall lifestyle. Actual demand flexibility-relevant behavior can provide insights for participation trends. Abstract: Residential demand flexibility (DF) could save the U.S. electric grid up to 10 GW of peak demand while supporting increased amounts of renewable generation. However, less than 40% of the estimated DF peak reduction capacity is currently realized, and less than 8% of American households are enrolled. These low participation rates are combined with high rates of "overriding" a DF event and eventual opt-outs among enrolled customers. There is still not a comprehensive understanding of the drivers of DF participation and occupant interaction with DF program signals. We, therefore, present a novel survey processing framework to assess occupant DF-relevant behavior from the American Time Use Survey (ATUS). Using the framework, we summarize both the extensive and intensive behavior of more than 200, 000 ATUS respondents (2003–2018 data) and provide insights on the DF-relevant behavior of residential occupants, which is generally overlooked in the literature. We use the framework to identify the activity priorities of residential occupants in the United States during different DF-relevant periods (critical peak, peak, and off-peak). These preferred activities capture overlooked routine behaviors that could be barriers to DF participation, if ignored, and might explain the high levels of overrides often exhibited by participants of demand response.